A strategy for purifying glutathione S-transferase in the presence of sodium dodecyl sulfate - Boisselier, Elodie (BioTechniques, 2011)
Glutathione S-transferase (GST) is widely used to prepare and purify GSTtagged fusion proteins. Although GST improves protein solubility, detergents must often be used to achieve protein solubilization from bacterial lysates. However, purification of GST by affinity chromatography cannot be achieved in the presence of even low concentrations of the detergent sodium dodecyl sulfate (SDS). Here we show that 2-methyl-2,4-pentanediol (MPD) can prevent SDS from interfering with purification of GST, thus enabling purification of proteins that require SDS to improve their solubility